Análise das relações de poder na descentralização da vigilância sanitária do município de Natal/RN - Barros, Rosires Magali Bezerra de (2016)
Sanitary surveillance is a promotion action in the field of collective health, with activities aimed at controlling the production and sale of goods, products and services, with a view to eliminating or minimizing risks, for the health of the community. The objective of this study is to analyze the power relations established in the decentralization of sanitary surveillance in the city of Natal / RN and to unveil this process from the analysis of the policies formulated by the federal sphere, from the power relations evidenced between the federative entities and the actors involved in this process. This research was developed in three stages, the first was the study of theoretical and empirical reference for the analysis of the policy of decentralization of health surveillance; The second was the construction of the report and the analysis of how the decentralization of sanitary surveillance in Natal / RN occurred and the third contemplated the analysis of the power relations between the federative entities in this municipality, in the light of the theoretical reference and the decentralization policy in the parents. The methodological approach is qualitative, descriptive and exploratory. The case study was based on documentary research and interviews with key informants who held management positions in health surveillance in Natal and Rio Grande do Norte State. The review of the literature on the decentralization of health surveillance was carried out based on the metassynthesis of the publications from 1990 to 2014, with the support of IRAMUTEQ software. The analysis of the interviews was carried out with the support of this software and with the instruments of the Bardin content analysis. The results show that the decentralization of sanitary surveillance in Natal happened from a correlation of forces, between State and Municipality, marked, more frequently, by moments of tension. These power relations were asymmetric and the advances and setbacks, in this process, happened in function of these relations. At the end of this study, it was possible to expand the understanding of the decentralization of sanitary surveillance in the city of Natal and to contribute to the understanding of this guideline in the field of sanitary surveillance, since this process has not yet been concluded in Natal, nor in the rest from the country.